2016
DOI: 10.3390/w8030076
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria Removal from Stormwater Runoff Using Tree Filters: A Comparison of a Conventional and an Innovative System

Abstract: Non-point source pollution of stormwater contributes high contaminant loads into surface water bodies and poses a threat to the ecosystem, public health and economy. Although (pre)treatment standards have not been introduced at the federal level, Rhode Island (RI) has set minimal contaminant reduction standards for stormwater using structural best management practices (BMP). As BMP performance depends highly on geographical location and climate, and the Northeastern United States experiences broad ranges of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…It has been found that these treatment units also reduce the number of bacteria and viruses [22]. There can also be antimicrobial amended layer added to the sand filter system [36,37]. In larger treatment units, such as public buildings e.g., schools and hotels or where the systems are shared between several households, disinfection of effluent can be a good option; it has been recommended that peracetic acid is a good choice as a disinfectant [8].…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that these treatment units also reduce the number of bacteria and viruses [22]. There can also be antimicrobial amended layer added to the sand filter system [36,37]. In larger treatment units, such as public buildings e.g., schools and hotels or where the systems are shared between several households, disinfection of effluent can be a good option; it has been recommended that peracetic acid is a good choice as a disinfectant [8].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, runoff from residential and commercial parcels and properties can constitute a considerable proportion of stormflow volume, yet holds much potential for management with LID and GI techniques applied to parcels, neighborhoods, and in right‐of‐way areas (Green et al ., ; Shuster and Rhea, ; Herrmann et al ., ; Jarden et al ., ; Schifman et al ., ; Shuster et al ., ). Any type of GI installation is a hydrologic intervention, and more often than not, requires hydrologic modeling to support the planning and design process.…”
Section: Introductionmentioning
confidence: 97%
“…Other media amendments, such as expanded shale (ES) and red cedar wood chips (RC), have also been investigated as potential biofilter amendments. Like other amendments described above, the introduction of ES and RC for microbial removal is inspired by their promise in removing organic contaminants and heavy metals from urban stormwater [68][69][70]. The efficacies of these amendments are found to be dependent on the influent microbial concentration.…”
Section: Amendments To Sand Biofiltersmentioning
confidence: 99%
“…Importantly, the effectiveness of antimicrobial modification depends on the antimicrobial loading (mg/g of filter media), temperature, and the residence time of stormwater. Recently, a full-scale field-study with TPA-modified RC and ES was attempted [69] using a tree box filter-a biofilter installed beneath a tree. Unlike the laboratory-scale study, TPA-modified biofilters in the field did not demonstrate any Water 2016, 8, 600 9 of 24 significant improvement of E. coli removal compared to the biofilters containing unmodified RC and ES, possibly due to reduced hydraulic residence time (too short for antimicrobial action to occur).…”
Section: Surface Modification Of the Filter Media And Amendmentsmentioning
confidence: 99%